LMI Mengembangkan Public Speaking Skill Berbicara Di Depan Umum - Sevi Arya Fatma; Saifuddin Zuhri (Jurnal Kabar Masyarakat, 2023)
Communication is something that cannot be separated from various human activities. This is based on the need to convey and receive information. One of the communication skills that everyone needs is public speaking skills. In order to develop public speaking skills, LMI organizes public speaking training activities that present speakers who are experts in the field of public speaking. The purpose of research on these activities is to see the enthusiasm of the community and the impact of public speaking training activities. This study used qualitative research methods. The results of the public speaking training activities show that the community, especially young teachers and preachers are very enthusiastic about developing public speaking skills and having a good impact on self-confidence when practicing public speaking. Therefore, it appears that public speaking training is put to good use by the community to continue to develop skills in public speaking.